Kalliope Bairami, Large Scale Rhodian Sculpture of Hellenistic and Roman Times - Kazakidi, Natalia (Journal of Hellenistic Pottery and Material Culture, 2019)
The issue of sculpture workshops and centres of production has been the focus of much scholarly attention since Andreas Linfert’s first systematic study on the subject. The systematic documentation and publication of sculpture with a shared provenance is essential to advancing research in this respect. This is the context in which the objectives of this study, which represents Bairami’s doctoral thesis, were framed. Although this study has the rather general title of ›Large Scale Rhodian Sculpture of Hellenistic and Roman Times‹, the catalogue of sculptures that forms the basis of the various chapters includes 105 works of sculpture in all, of which 57 have not previously been published. These are works that have entered the collection of the Rhodes Archaeological Service in the last forty-five years or so.